Analisis Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), dan Loan To Deposit Ratio (LDR) Terhadap Firm Value Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Raymond F Rombot; Andreas Randy Wangarry; Antonius Tandi; Maykel Tampenawas4 (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
This study aims to examine the effect of capital adequacy ratio, non performing loan, and loan to deposit ratio on the firm value of banking companies. This study employed secondary data in the form of financial statements of banking companies from 2016-2020. The population in this study are banking companies that have been listed on the Indonesia Stock Exchange (IDX), as many as 30 issuers of banking companies. The sample selection in this study used purposive sampling method. The analytical method used in this research is multiple linear regression. The results showed partially, the capital adequacy ratio variable had a significant effect on the Firm Value of banking companies, while the non- performing loan and loan to deposit ratio variables had no significant effect on the Firm Value of banking companies. Keywords: capital adequacy ratio, non performing loan, loan to deposit ratio, dan firm value